Pengaruh Kompensasi Terhadap Kinerja Karyawan Kebersihan Pada Dinas Perlindungan dan Pengelolaan Lingkungan Hidup Kota Sorong - Januaris Pikei; Audi Satria; Reza Billy Lengkong (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The classic and complex problem that plagues the world of business and work is compensation. As is well known, one of the main factors influencing the improvement of employee performance is proper compensation given by companies or government agencies to their employees or employees. Indonesian labor law already regulates compensation. The government, through the Ministry of Manpower, continues to emphasize all companies and government agencies in Indonesia to comply with and implement the laws of the Unitary State of the Republic of Indonesia. Employees at the Remu market Environmental Protection and Management Service in Sorong, Southwest Papua, are the subject of this study. The purpose of this study is to determine the extent to which compensation can improve employee performance. 26 market cleaning employees were the subject of the quantitative research conducted. Data were collected through questionnaires and analyzed using SPSS version 24.